(untitled) (Jurnal Teknologi Industri Pertanian, 2012)
ABSTRACT A synthesis of copolymer anethole-divinylbenzene (DVB) by cationic polymerization followed with sulfonation reaction has been done. The aim of this research is to synthesize of copolymer as cation exchange resin. Cationic copolymerization of anethole-DVB was done by using BF3O(C2H5)2 catalyst, without medium and under nitrogen atmosphere condition. Sulfonation reaction was done by H2SO4 reagent and Ag2SO4 catalyst. The structural prediction of the synthesis yield was done by functional groups analysis with FTIR spectrophotometer, while characterization of copolymer was done by thermal analysis using DTA (Differencial Thermal Analysis). The relative molecular weight of copolymer was determined by viscometry method. The copolymer tested as cation exchange resin by exchanging H+ (SO3H group) with Ca2+ in a column. The level of cationic exchanging capacity of copoly(anethole-DVB) sulfonat resin was determined by measuring the Ca2+ that replace H+ at resin using AAS. Result of copolymerization of anethole-DVB was moon green coloured solid with relative molecular weight equal to 24,789 g/mole. Result of sulfonation was purple colored solid. Result of DTA analysis showed that degradation of copoly(anethole-DVB) begin at 550 oC, while degradation of copoly(anethole-DVB) sulfonate begin at 840 oC. AAS analysis showed the exchanging capacity of copoly(anethole-DVB) sulfonate equal to 296.756 meq Ca2+ ion/g of copolymer. Keywords : Anethole, cationic copolymerization, sulfonation reaction, cation exchange resin, copoly(anethole-DVB) sulfonate